2018
DOI: 10.4172/neuropsychiatry.1000358
|View full text |Cite
|
Sign up to set email alerts
|

A Tryptophan Hydroxylase Inhibitor Decreases Hepatic FGF21 Expression and Circulating FGF21 in Mice Fed A High-Fat Diet

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We have previously reported that treatment with PCPA for 3 days suppresses daily food intake, body weight gain and the increases in plasma FGF21 levels and insulin levels in C57BL6J mice fed a high-fat diet [19]. Moreover, treatment with PCPA significantly increases expression of hepatic Nrf2 and decreases expression of hepatic FGF21 in mice fed a high-fat diet [19].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously reported that treatment with PCPA for 3 days suppresses daily food intake, body weight gain and the increases in plasma FGF21 levels and insulin levels in C57BL6J mice fed a high-fat diet [19]. Moreover, treatment with PCPA significantly increases expression of hepatic Nrf2 and decreases expression of hepatic FGF21 in mice fed a high-fat diet [19].…”
Section: Discussionmentioning
confidence: 95%
“…We have previously reported that treatment with PCPA for 3 days suppresses daily food intake, body weight gain and the increases in plasma FGF21 levels and insulin levels in C57BL6J mice fed a high-fat diet [19]. Moreover, treatment with PCPA significantly increases expression of hepatic Nrf2 and decreases expression of hepatic FGF21 in mice fed a high-fat diet [19]. Despite decreases in daily food intake and body weight, treatment with PCPA had different effects on plasma FGF21 levels and expression of hepatic FGF21 and Nrf2 in mice fed a high-fat diet and Research Katsunori Nonogaki Figure 1: Plasma FGF21 levels (A) and hepatic FGF21 expression (B) in 9 wk-old db/db mice and C57BL6J mice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to what we observed in our study, the TPH1 inhibitor (LX‐1031) has been shown to ameliorate irritable bowel syndrome and chronic diarrhea through reduced 5‐HT levels . Moreover, a study has shown that p‐CPA decreases liver FGF21 expression/levels of fibroblast growth factor 21 in a mouse model of high‐fat diet, suggesting the potential role of 5HT in modulating LF in nonalcoholic fatty liver disease/nonalcoholic steatohepatitis patients …”
Section: Discussionmentioning
confidence: 99%
“…(45) Moreover, a study has shown that p-CPA decreases liver FGF21 expression/levels of fibroblast growth factor 21 in a mouse model of high-fat diet, suggesting the potential role of 5HT in modulating LF in nonalcoholic fatty liver disease/ nonalcoholic steatohepatitis patients. (46) We next performed in vitro experiments aimed to demonstrate that the autocrine/paracrine action of serotonin on biliary proliferation/liver fibrosis is not attributed to secondary in vivo effects, but rather to a direct interaction with both cholangiocytes and HSCs.…”
Section: Discussionmentioning
confidence: 99%